Women Empowerment in Tourism: Special Reference to Pokhara Metropolitan City - Palikhe, Amin (Journal of Nepalese Business Studies, 2018)
This article examines women empowerment in tourism with reference to the Pokhara Metropolitan City, Nepal. The major objective is to identify the women in tourism, their situation, problem, and obstacle and future perspective in the tourism industry. The descriptive and analytical research design is used. Primary and secondary sources of data are used. Fifty-two samples have been taken from the tourism industry (hotel, lodge, travel, and trekking) and a questionnaire distributed to women. Some women are entrepreneurs and some are employees in the tourism field in Pokhara. Women are gradually being motivated to involve themselves in tourism-related business. These days, women’s contribution does not equate males when they are compared. Most of the women work at a lower level and they are satisfied with their work and their contribution. Women face different obstacles that hamper them to move, initiate and run their business. Women have better potentiality in different tourism sectors like direct and indirect, such as framing, planting, travel, and trekking, rural tourism, home stay, medication, and hospitability. But they have various causes and reasons to work at a lower level.